Nonprofit essentials : the capital campaign - Walker, Julia Ingraham (AFP fund development series., 2005)
Nonprofit Essentials provides a thorough and practical overview of the process of planning and managing a capital campaign. In lively discussions, independent consultant Julia Walker shares the tips, techniques, and programs that have helped her raise more than 600 million in capital campaigns.